PERENCANAAN SDM DALAM PENDIDIKAN ISLAM UNTUK MEMPERSIAPKAN GENERASI RABBANI - Desi Fatma; Jamilus Jamilus (Universitas Bina Taruna Gorontalo, 2024)
This research aims to find out that Human Resource Planning (HR) in Islamic education is an important aspect that plays a major role in forming a quality Rabbani generation. This research uses a literature study or literature study method. In this competitive era and rapid technological progress, the presence of quality human resources is very vital for Islamic educational institutions. The HR planning process involves systematic identification, procurement, development and evaluation of human resources to ensure availability, quality and effective management. The Rabbani generation is a generation that has a deep understanding of Islam, has noble character, has broad knowledge and is able to apply its values. Islam in everyday life. Human resources in Islamic educational institutions have a big role in forming the Rabbani generation by being role models, educating with patience and compassion, creating a conducive environment, imparting knowledge effectively, instilling Islamic values, guiding them to become leaders who have faith and noble character, providing motivation. , as well as collaborating with parents. The HR planning process involves identifying needs, procuring human resources through recruitment and placement, developing and educating human resources through training and coaching, as well as evaluating and controlling human resources to ensure maximum performance and contribution. Awareness of the importance of thorough HR planning and the role of effective HR in forming the Rabbani generation is the main key in advancing Islamic educational institutions and building a better future for the people and nation.